A possible link between recurrent upper respiratory tract infections and lower cytokine production in patients with Q fever fatigue syndrome. Issue 7 (9th May 2019) - Raijmakers, Ruud P.H.; Jansen, Anne F.M.; Keijmel, Stephan P.; van der Meer, Jos W.M.; Joosten, Leo A.B.; Netea, Mihai G.; Bleeker‐Rovers, Chantal P.
Abstract: Besides fatigue, many Q fever fatigue syndrome (QFS) patients also complain of frequently recurring upper respiratory tract infections with severe symptoms. We investigated whether immunologic dysregulation contributes to these complaints. Cytokine and chemokine production was measured after stimulating monocytes of QFS patients and age‐ and sex‐matched healthy controls with LPS and several viral ligands. The H3K4me3 mark of open chromatin was measured at the promoter regions of cytokines and chemokines that differed significantly from healthy controls. Monocytes of QFS patients produced significantly less TNF‐α ( p = 0.032), IL‐1β (0.004, 0.024, and 0.008), IL‐6 (0.043), RANTES (0.033), IP‐10 (0.049), MCP‐1 (0.022), IL‐ 13 (0.029), and IL‐10 (0.026) than healthy controls when stimulated with various ligands. H3K4me3 expression was significantly lower in QFS patients than in healthy controls on the promoter regions of IL‐1β ( p = 0.004), MCP‐1 (<0.001 and <0.001), IP‐10 (<0.001), IL‐10 (0.041), and IL‐13 (<0.001, <0.001, and 0.001). QFS patients showed diminished cytokine responses to various stimuli compared to age‐ and sex‐matched healthy controls, likely due to epigenetic remodeling and long‐term memory as a result from the acute Q fever infection. This might explain the upper respiratory tract ailments in QFS. Abstract : Circulating monocytes of Q fever fatigue syndrome patients with recurrent upper respiratory tract infections produce less cytokines compared to those of healthy controls when stimulated with viral ligands, possibly due to epigenetic remodeling following the acute Q fever infection.